Recent Developments in Wine Tartaric Stabilization - Cabrita, Maria João (2016)
Tartrate precipitation is still a relevant subject in Enology, being one of the most common problems of wine physical-chemical instability. Potassium bitartrate and calcium tartrate precipitations are undesirable phenomena which can occur in bottled wines, especially when these are stored at low temperatures. The occurrence of tartrate salt crystals (potassium hydrogen tartrate – KHT and calcium tartrate – CaT) in bottles has severe consequences in the final aspect of the wine and therefore on the consumer’s acceptance, making tartrate wine stabilization virtually mandatory before bottling. Currently, several solutions to prevent this haze are available: subtractive methods including the conventional cold treatments that promote the cristalization of KHT, removal of potassium and calcium ions either by electrodialysis or ion exchange resins; and additive methods such as the addition of carboxymethylcellulose, mannoproteins or metatartaric acid. For monitoring the KHT stability, several analytical methods have been developed based on conductivity evaluation, namely the mini-contact test and the saturation temperature measurements (TS). These methods will also be revisited, aiming to raise awareness of their utility as tools in quality control of wines. This review addresses tartrate precipitation subject and the most recent preventive solutions available, pointing out the advantages and drawbacks of each one, and its impact on the final characteristics of the wine.